Pengaruh Literasi Keuangan dan Gaya Hidup terhadap Pengelolaan Keuangan DAI Bekasi pada Masa Pendemi Covid 19 - Rikza Maulan; Moh Khoirul Anam; Muhammad Choirin; Laila Yumna; Bisri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of financial literacy and lifestyle on financial management during the pandemic. During the pandemic, there were restrictions on activities and economic activities so that people had limited income and were required to manage their money efficiently and even be required to generate additional income. So that there is a demand for expertise in financial management. To analyze this phenomenon, research was carried out using quantitative methods. Data collection was carried out by distributing questionnaires to selected respondents. The results of the study show that financial literacy partially affects financial management, and lifestyle affects financial management. Simultaneously, financial literacy and lifestyle affect financial management. The determination coefficient shows 0.633 which means that the independent variable determines the dependent variable of 63.3% This influence is quite strong because it exceeds 50%. while the remaining 36.3% is determined by other variables.